PENGEMBANGAN MODEL ROUND CLUB MELALUI APLIKASI GOOGLE SITE PADA MAPEL SEJARAH KEBUDAYAAN ISLAM DI MTSN 5 PADANG PARIAMAN - Muhammad Aldian Syah; Ahmad Sabri; Sasmi Nelwati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this research is to develop and analyze the implementation of the Round Club learning model through the integration of Google Site as a digital platform to enhance student engagement in Islamic Cultural History (Sejarah Kebudayaan Islam - SKI) learning. This study adopts a qualitative approach with a case study design, focusing on eighth-grade students at MTs 5 Padang Pariaman. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The research findings indicate that the integration of the Round Club model with Google Site provides a learning environment that promotes student collaboration, active participation, and reflective learning. The model encourages equitable contribution within group discussions and fosters a project-based learning culture that is both contextual and meaningful. The use of Google Site further enhances student autonomy by offering a digital space to document, organize, and present learning artifacts collaboratively. Additionally, it improves digital literacy skills and builds student confidence in public presentation. This study concludes that the Round Club model supported by Google Site is an effective pedagogical innovation for increasing student engagement, especially in religious and humanities education contexts. The findings also suggest the model’s potential for broader application in digital-based learning to meet the demands of 21st-century competencies.